Effects of Timber Harvesting and Related Management Practices on Water Quality in Forested Watersheds - Sopper, William E. (Journal of Environmental Quality, 1975)
Abstract Undisturbed forested watersheds are generally recognized as a primary source of high‐quality water. The physical and chemical nature of these waters fluctuate constantly in response to natural stresses but are most influenced by man's activities. Three major forest land management activities—timber harvesting, fertilization, and herbiciding—which may have an adverse affect on water quality are reviewed. In general, research results indicate that nutrient losses, particularly nitrogen, following forest clearcutting are small to negligible. Similarly, forest fertilization studies indicate that nitrogen concentrations in streams are not drastically increased. Large areal applications of selected herbicides in the West have demonstrated that, if carefully applied, they can be used without impairment of water quality.
Keywords: Ouvrage_Collectif_Numéro1